Current Problems of Digitalization in Russia: Building Knowledge Economy - Elena SHKARUPETA; Diana SAVON; Andrey SAFRONOV; Galina KRUZHKOVA; Dina Borisova (Communications of International Proceedings, 2021)
The movement along the way of managing the development of industrial companies requires the joint efforts of all participants. It is necessary to overcome a significant number of barriers. Only in this way the industrial complexes and the national economy of Russia as a whole will be able to move to a new stage in the development of the digital economy, to ensure the competitiveness of products of national production, both on the domestic and global markets. Thus, the development environment under digital transformation changes its state to the “digital environment for the development of industrial companies” due to infrastructure and institutional changes.
Keywords: Digitalization; Knowledge Economy; Russia; Problems; Development.